Quantitative Defect Detection on the Underside of a Flat Plate Using Mobile Thermal Scanning. (2017) - Tan, Y.C.; Chiu, W.K.; Rajic, N.
Abstract: Computational simulation is used to investigate mobile thermal scanning for the detection and quantitative measurement of defects along the underside of a steel plate. Comparisons are made between mobile and stationary heating regimes. The Full Width Half Maximum (FWHM) method is applied to determine the defect size, and the second order peak derivative method to determine the defect depth. Results for near-surface defects showed good accuracy, however errors are shown to grow with increasing defect depth.